2013
DOI: 10.2176/nmc.53.157
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Outcomes in Young Adults With Aneurysmal Subarachnoid Hemorrhage

Abstract: Subarachnoid hemorrhage (SAH) is rare in young adults and little is known about aneurysms in this subgroup. The effect of clinical and prognostic factors on the outcome based on the Glasgow Outcome Scale (GOS) scores and the predictors of unfavorable outcomes were analyzed in young adults with aneurysmal SAH. A retrospective review of the clinical parameters, including age, sex, hypertension, smoking status, hyperlipidemia, location of the cerebral aneurysm, size of the aneurysm, multiplicity, perioperative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
3
21
2
Order By: Relevance
“…The Hunt and Hess grade has been shown to be an independent predictor of poor outcomes in aneurysmal subarachnoid hemorrhage, and this was also noted in our study 15. To our knowledge, this is the first report to show Hunt and Hess grade as an independent predictor of IAVT.…”
Section: Discussionsupporting
confidence: 87%
“…The Hunt and Hess grade has been shown to be an independent predictor of poor outcomes in aneurysmal subarachnoid hemorrhage, and this was also noted in our study 15. To our knowledge, this is the first report to show Hunt and Hess grade as an independent predictor of IAVT.…”
Section: Discussionsupporting
confidence: 87%
“…Chotai et al found in a univariate regression analysis of the outcomes at discharge that the age of the patient at the time of presentation and male gender were predictors of an unfavorable outcome. A multivariate regression analysis showed the independent effects of gender on the outcome at discharge in 108 young adult patients (6). Although there are also reports suggesting that age and sex have no prognostic value (3,11,14,20).…”
Section: Age and Gendermentioning
confidence: 93%
“…Chotai et al (6) also found that the size of the aneurysm and the presence of multiple aneurysms were associated with unfavorable outcomes. In young adult patients, the size of an aneurysm and the presence of multiple aneurysms were found to be predictors of outcome at mean two years of follow up (6). Similar to other studies, …”
Section: Localization and Diameter Of Aneurysmmentioning
confidence: 97%
See 2 more Smart Citations